Analisis Keandalan Pembangkit Listrik Tenaga Mini Hidro Orya-Genyem Berdasarkan Load of Loss Probability: Reliability Analysis of Orya-Genyem Mini Hydroelectric Power Plant Based on Load of Loss Probability - Anne Sihombing; Joni Joni; Yane Ansanay; Enos Karapa; Herbert Innah; Prihananto Setiadji; Johni Jonatan Numberi; Tiper K. M. Uniplaita (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2023)
Electricity is crucial for supporting development, the economy, and human well-being, thus leading to an increasing demand for electrical energy. Therefore, power plants are planned and constructed to be as economically viable as possible. In line with the principles of affordability, security of supply, and acceptability, to ensure long-term capacity demand and reliability. The reliability of the power plant is measured using the Load of Loss Probability (LOLP) index, which assesses the probability of components functioning satisfactorily to meet demand. The objective of this research is to analyze the reliability of PLTM Orya-Genyem based on the Load of Loss Probability (LOLP) index. The research methodology is qualitative, commencing with the collection of secondary data, followed by LOLP calculations to obtain reliability information. LOLP index for PLTM Orya-GGenyem is 0,4204%, equivalent to 1,5346 days per year, exceeding the PLN standard of 1 day per year. This indicates a lack of reliability in the power plant. Research findings reveal that daily power demand increases by 0,054 MW for every 1% increase in time. Assessment indicates that peak load surge factor is not the cause of the high LOLP value in PLTM Orya-Genyem. Instead, outages are the cause. The assessment shows that there were 72 disturbances of maintenance outages for PLOG-TA-01 and 145 disturbances of system adjustment outages for PLOG-TA-02. Other outages that happen include low water elevation, water storage duration, floods (accumulated debris), transmission work, blackouts, network disturbances, forced outages, planned outages, sedimentation dredging, water drainage, water filling, performance testing, and maintenance during plant operation.